The Old Man and Linguistic Politeness in the Comedies of Plautus - Berger, Łukasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The aim of the article is to study the conversational behaviour of the Plautine old men in light of (im)politeness theory. The analysis concerns those scenes of salutatio and advice-giving where one of the speakers is a senex, in order to examine features of his linguistic characterisation.